A COMPARATIVE ANALYSIS OF GRADE 7 AND GRADE 8 STUDENTS’ CREATIVE THINKING SKILLS USING THE EXPERIENTIAL LEARNING MODEL - Sam Hermansyah; Roni Roni; Jimmy Cromico; Firman Saleh (La Ogi : English Language Journal, 2026)
This study aims to conduct a comparative analysis of Grade 7 and Grade 8 students’ creative thinking skills through the implementation of the Experiential Learning model at SMPN 2 Pangsid. The research employed a quantitative approach using a pretest–posttest comparative design. The participants consisted of 20 students selected through purposive sampling, with 10 students from Grade 7A and 10 students from Grade 8A. Data were collected using a creative thinking test based on four indicators: fluency, flexibility, originality, and elaboration. The collected data were analyzed using descriptive statistics, normality tests, and Independent Samples t-Test with the assistance of SPSS software. The findings revealed that there was a significant improvement in students’ creative thinking skills after the implementation of the Experiential Learning model in both grades. Grade 7 students demonstrated a higher and more consistent increase in posttest scores compared to Grade 8 students. The statistical analysis indicated no significant difference in pretest scores between the two grades, while a significant difference was found in posttest results, confirming the effectiveness of the Experiential Learning model in enhancing creative thinking skills. These results suggest that Experiential Learning is an effective instructional approach for fostering students’ creative thinking through active engagement and meaningful learning experiences.